2003
DOI: 10.1121/1.1564013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prosodic boundary on /aC/ sequences: articulatory results

Abstract: This study presents EMA (electromagnetic articulography) data on articulation of the vowel /a/ at different prosodic boundaries in French. Three speakers of metropolitan French produced utterances containing the vowel /a/, preceded by /t/ and followed by one of six consonants /b d g f s S/ (three stops and three fricatives), with different prosodic boundaries intervening between the /a/ and the six different consonants. The prosodic boundaries investigated are the Utterance, the Intonational phrase, the Accent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
3
54
2
5
Order By: Relevance
“…Phrase final and initial articulatory lengthening have been observed to increase cumulatively for larger prosodic boundaries (phrase finally: Byrd and Saltzman, 1998;Byrd, 2000;Cho, 2006;Tabain, 2003;Tabain and Perrier, 2005; and phrase initially: Byrd and Saltzman, 1998;Cho and Keating, 2001;Fougeron, 2001;Cho, 2006;Tabain, 2003;Keating et al, 2004), though there is individual variation. Articulatory studies have also shown there to be less temporal overlap between articulations separated by a boundary or adjacent to a boundary (McClean, 1973;Byrd et al, 2000;Byrd and Saltzman, 1998;Byrd, 2000; see also Hacopian, In the spatial domain, Fougeron and Keating (1997) and others show the effects of increased linguapalatal contact to be cumulative-higher (stronger) prosodic boundaries induce greater linguapalatal contact, both phrase initially (Fougeron and Keating, 1997;Cho and Keating, 2001;Fougeron, 2001;Keating et al, 1999;Tabain, 2003;Keating et al, 2004) and phrase finally (Fougeron and Keating, 1997 [although their results are less consistent across speakers than their results for phrase-initial effects], Keating et al, 1999; see also Hacopian, 2003;Tabain, 2003).…”
Section: A Articulatory Studies On Phrase Boundary Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phrase final and initial articulatory lengthening have been observed to increase cumulatively for larger prosodic boundaries (phrase finally: Byrd and Saltzman, 1998;Byrd, 2000;Cho, 2006;Tabain, 2003;Tabain and Perrier, 2005; and phrase initially: Byrd and Saltzman, 1998;Cho and Keating, 2001;Fougeron, 2001;Cho, 2006;Tabain, 2003;Keating et al, 2004), though there is individual variation. Articulatory studies have also shown there to be less temporal overlap between articulations separated by a boundary or adjacent to a boundary (McClean, 1973;Byrd et al, 2000;Byrd and Saltzman, 1998;Byrd, 2000; see also Hacopian, In the spatial domain, Fougeron and Keating (1997) and others show the effects of increased linguapalatal contact to be cumulative-higher (stronger) prosodic boundaries induce greater linguapalatal contact, both phrase initially (Fougeron and Keating, 1997;Cho and Keating, 2001;Fougeron, 2001;Keating et al, 1999;Tabain, 2003;Keating et al, 2004) and phrase finally (Fougeron and Keating, 1997 [although their results are less consistent across speakers than their results for phrase-initial effects], Keating et al, 1999; see also Hacopian, 2003;Tabain, 2003).…”
Section: A Articulatory Studies On Phrase Boundary Effectsmentioning
confidence: 99%
“…Articulatory studies show that at phrase edges "gestures get larger, longer, and further apart" (Byrd and Saltzman, 2003, p. 159;Byrd et al, 2000). Articulations are spatially more extreme and temporally longer (Edwards et al, 1991;Beckman and Edwards, 1992;Fougeron and Keating, 1997;Byrd and Salzman, 1998;Fougeron, 2001;Cho, 2006;Cho and Jun, 2000;Cho and Keating, 2001;Tabain, 2003;Keating et al, 2004;Tabain and Perrier, 2005).…”
Section: A Articulatory Studies On Phrase Boundary Effectsmentioning
confidence: 99%
“…It is also the case that position affects duration (Oller, 1973;Edwards et al, 1991;Tabain, 2003;Cho, 2006), which in turn affects lenition (Section 1.3.1). Consequently we will be interested in this study to probe whether the contributions to lenition of duration and position are to some degree independent.…”
Section: Domain Position Effectsmentioning
confidence: 99%
“…Além disso, alguns estudos também constataram que quanto mais alto o domínio prosódico, maior é a duração (cf. TABAIN, 2003;KEATING et al, 2003). Neste caso, a previsão seria de uma variação na duração das sílabas de 'filho' apenas na aposição não-local, por serem próximas à fronteira de frase fonológica.…”
Section: Introductionunclassified